1984
DOI: 10.1073/pnas.81.23.7284
|View full text |Cite
|
Sign up to set email alerts
|

Salt-induced Z-A-Z transition sequence in the mixed ribo-deoxyribo copolymer poly(rG-dC) X poly(rG-dC).

Abstract: The left-handed helical conformation of various polynucleotides has been seen in solution at higher salt concentration than has the right-handed helical conformation of the corresponding polymer. We report here, however, studies of conformational transitions in the mixed polymer poly-(rG-dC)-poly (rG-dC). This polynucleotide appears to exist in a Z conformation under low-salt conditions, converts to an A helix at intermediate salt, and reverts to a left-handed helix at high-salt concentration.The left-handed h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Another important consequence of s‐NAP complexation into m‐NAP is the strong increase of electrostatic forces that the latter compound exerts on DNA. It is known that electrostatic forces play a greater role in the A–Z transition than they do in the B–Z transition, because the difference in the linear charges density is greater between the A and the Z forms than between the B and the Z forms [51]. For this reason, we constructed a model in which s‐NAP interacts with A‐DNA and, among the non‐Z→Z transitional possibilities, we chose the A→Z possibility (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another important consequence of s‐NAP complexation into m‐NAP is the strong increase of electrostatic forces that the latter compound exerts on DNA. It is known that electrostatic forces play a greater role in the A–Z transition than they do in the B–Z transition, because the difference in the linear charges density is greater between the A and the Z forms than between the B and the Z forms [51]. For this reason, we constructed a model in which s‐NAP interacts with A‐DNA and, among the non‐Z→Z transitional possibilities, we chose the A→Z possibility (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The aggregation of s-NAP into m-NAP, however it occurs, brings about a significant increase in the charge on the DNA. It was shown that electrostatic forces play a greater role in A -Z transition than they do in B -Z transition, because the difference in linear charge density is greater between the A and the Z forms than between the B and the Z forms (18). Thus, we presented a model in which s-NAP interacts with A-DNA, and the s-NAP aggregation into (or its replacement with) m-NAP induces an A to Z transition on DNA (Fig.…”
Section: Naps Regulate Dna Form Transitionsmentioning
confidence: 99%
“…The far ultraviolet CD spectrum of poly (rG-dC)Opoly (rG-dC) in the presence of (tetramethyl ammonium ion] ranging from 0.5 mM to 3 M is very similar to that for the Z form of the polynucleotide previously seen in solutions of very low or very high [NaCl] (1). To be certain that the CD spectrum did reflect a Z form the circular dichroism spectrum of the polymer was recorded down to 180 nm.…”
Section: Resultsmentioning
confidence: 69%
“…Instead, as shown in Fig. 2, both ions caused the transition of the polymer from the low salt Z form to the A form at about 2-5 mM counterion concentration, more efficiently than the primary amine Tris (1). Tetrabutyl amonium ion, the largest counterion we tested, would not support the low K.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation